Nutritional management of individuals with Huntington''s disease: nutritional guidelines. (February 2012) - Brotherton, Ailsa; Campos, Lillian; Rowell, Arleen; Zoia, Vanessa; Simpson, Sheila A; Rae, Daniela
SUMMARY The delivery of good nutritional care is a fundamental element of the management of individuals with Huntington''s disease and all patients with Huntington''s disease will, at some time, need dietary intervention because of the sequela of the disease; yet there are no European nutritional guidelines. The European Huntington''s Disease Network Standards of Care Dietitians Group has brought together expert dietitians from across Europe to produce nutritional guidelines to improve the nutritional management of individuals with Huntington''s disease. The guidelines were developed to promote optimal nutritional screening, assessment and management of individuals throughout all stages of the disease, with the aim of improving the standard of nutritional care delivered. Literature was systematically searched in an attempt to ensure that the recommendations are based on sound evidence and where evidence is lacking, specific guidance is based on consensus expert dietetic opinion. The provision of nutritional care varies widely between countries. Implementation of these nutritional guidelines across Europe should improve the quality of nutritional care delivered to individuals with Huntington''s disease.